Implementation of School Quality Management in Indonesia - Yulia Ainur Rofiqoh; Istikomah Istikomah; Hidayatulloh Hidayatulloh (International Consortium of Education and Culture Research Studies, 2020)
Every educational institution which is engaged in services and society, must be entitled to the goals in accordance with the institutions that can achieve progress and success of other educational institutions. Therefore educational institutions must be able to create schools that are innovative, innovative and of high quality. This is done competing with other educational institutions, and creating quality schools. This research tries to. Through this research, it is expected to be a reference for schools.